2019
DOI: 10.1186/s12957-019-1652-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Human epidermal growth factor receptor-2 expression in patients with resectable gastric adenocarcinoma

Abstract: Background The purpose of this study was to investigate the correlation between human epidermal growth factor receptor 2 (HER2) overexpression and clinicopathologic factors and overall survival rate in patients who underwent curative gastrectomy for gastric adenocarcinoma. Methods Among patients who underwent curative gastrectomy for gastric adenocarcinoma at Inje University Paik Hospital from January 2012 to December 2015, 782 patients underwent an immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…16 Moreover, the OS rates was compared between 1521 low HER2 expression patients and 190 high HER2 expression patients and the results did not indicate a signi cant survival difference for 1-year OS (60.6% vs 61.5%), 3-year OS (51.3% vs 53.8%) or 5-year OS (26.6% vs 27.6%), which was consistent with the analysis in 810 Korean GC patients. 17 However, two other studies demonstrated that HER2 overexpression is associated with poor survival outcomes in 100 Iranian patients and 1148 Japanese cases with GC. 18,19 The reasons for the inconsistent results could be partly attributed to the heterogeneity of HER2 expression among different ethnic populations or the effects of sample size.…”
Section: Discussionmentioning
confidence: 98%
“…16 Moreover, the OS rates was compared between 1521 low HER2 expression patients and 190 high HER2 expression patients and the results did not indicate a signi cant survival difference for 1-year OS (60.6% vs 61.5%), 3-year OS (51.3% vs 53.8%) or 5-year OS (26.6% vs 27.6%), which was consistent with the analysis in 810 Korean GC patients. 17 However, two other studies demonstrated that HER2 overexpression is associated with poor survival outcomes in 100 Iranian patients and 1148 Japanese cases with GC. 18,19 The reasons for the inconsistent results could be partly attributed to the heterogeneity of HER2 expression among different ethnic populations or the effects of sample size.…”
Section: Discussionmentioning
confidence: 98%
“…ERBB2, generally named Her2, is amplified or overexpressed in 20-30% of invasive breast carcinomas [7]. Moreover, amplification and overexpression of Her2 gene has also been detected in ovarian and gastric cancer [8][9][10]. Her2 integrates firmly to other epidermal growth factor receptor family members to assemble a heterodimer, which reinforce kinase-mediated activation of downstream signaling pathways, such as PI3K/AKT activation and RET signaling, so as to facilitate the increment and metastasis of cancer cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…The gradient method was employed to weigh the connection strength between each pair of nodes and assess the independence and average degree connectivity of the assorted modules with different power values (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In this work, the value whose independence degree was greater than 0.8 for the first time was seems as the appropriate power value (β) to ensure a scale-free network.…”
Section: Co-expression Network Constructionmentioning
confidence: 99%
“…ERBB2, commonly referred to as HER2, encodes a member of the epidermal growth factor receptor family of receptor tyrosine kinases, it is amplified and/or overexpressed in 20-30% of invasive breast carcinomas [13]. Amplification and/or overexpression of this gene have also been reported in many other cancers including ovarian and gastric cancer [14][15][16]. ERBB2 binds tightly to other ligand-bound EGF receptor family members to form a heterodimer, stabilizing ligand binding and enhancing kinase-mediated activation of downstream signaling pathways, such as PI3K/AKT activation and RET signaling [17].…”
Section: Discussionmentioning
confidence: 99%